Low-Temperature Thermochronology of the Chatkal-Kurama Terrane (Uzbekistan-Tajikistan): Insights Into the Meso-Cenozoic Thermal History of the Western Tian Shan - Jepson, G.; Glorie, S.; Konopelko, D.; Gillespie, J.; Danišík, Martin; Mirkamalov, R.; Mamadjanov, Y.; Collins, A. (American Geophysical Union, 2018)
The Chatkal-Kurama terrane represents a key region in understanding the tectonic evolution of the western Tian Shan. In this contribution, we present new thermochronological data (zircon [U-Th-Sm]/He, apatite fission track, and apatite [U-Th-Sm]/He) and the associated thermal history models for 30 igneous samples from the Chatkal-Kurama terrane within Uzbekistan and Tajikistan (west of the Talas-Fergana Fault) and integrate our data with published data from the central Tian Shan (east of the Talas-Fergana Fault). The Chatkal-Kurama terrane experienced a phase of rapid cooling during the Triassic-Jurassic at ca. 225–190 Ma, which we interpret as a far-field response to the closure of the Palaeo-Asian Ocean or the accretion of the Qiangtang terrane on to the Eurasian margin. In the Late Jurassic to the Early Cretaceous, the Chatkal-Kurama terrane experienced a period of tectonic stability and denudation, before transitioning into a period of marine incursions of the Paratethys Sea. In contrast, fast cooling is recorded for the Kyrgyz central Tian Shan to the east of the Talas-Fergana Fault. The differing thermal histories at either side of the Talas-Fergana Fault suggest that the fault induced a topographic divide during the Late Jurassic-Early Cretaceous, with high relief in the east (Kyrgyz Tian Shan) and low relief to the west (Uzbek-Tajik Tian Shan). Finally, the Chatkal-Kurama terrane experienced renewed tectonic activity since ca. 30 Ma, related with the distant India-Eurasia collision and Pamir indentation. The Cenozoic reactivation induced crustal tilting of the Chatkal-Kurama terrane, progressively exposing deeper rocks to the southwest.